2016
DOI: 10.1146/annurev-pharmtox-010715-103910
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Validate and Manipulate RNA Targets with Small Molecules in Cells

Abstract: RNA has become an increasingly important target for therapeutic interventions and for chemical probes that dissect and manipulate its cellular function. Emerging targets include human RNAs that have been shown to directly cause cancer, metabolic disorders, and genetic disease. In this review, we describe various routes to obtain bioactive compounds that target RNA, with a particular emphasis on the development of small molecules. We use these cases to describe approaches that are being developed for target val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 96 publications
(111 reference statements)
0
43
0
Order By: Relevance
“…M l RA‐19a is not only the first l ‐aptamer to be evolved by using modified nucleotides during the in vitro selection process but also the first modified aptamer (of any type) to be selected against a structured RNA target. This approach opens a route to precise targeting of a wide range of structured RNAs, thus addressing a long‐standing challenge in RNA biochemistry and drug discovery . Furthermore, our results suggested that l ‐aptamers, like their native counterparts, benefit from an expanded chemical repertoire.…”
Section: Figurementioning
confidence: 74%
See 1 more Smart Citation
“…M l RA‐19a is not only the first l ‐aptamer to be evolved by using modified nucleotides during the in vitro selection process but also the first modified aptamer (of any type) to be selected against a structured RNA target. This approach opens a route to precise targeting of a wide range of structured RNAs, thus addressing a long‐standing challenge in RNA biochemistry and drug discovery . Furthermore, our results suggested that l ‐aptamers, like their native counterparts, benefit from an expanded chemical repertoire.…”
Section: Figurementioning
confidence: 74%
“…This approach opens ar oute to precise targeting of aw ide range of structured RNAs, thusa ddressing al ong-standingc hallenge in RNA biochemistry and drug discovery. [14] Furthermore,o ur results suggested that l-aptamers, like their native counterparts, benefitf rom an expandedc hemical repertoire. In the future,i t will be important to screen additional modifiedn ucleotides during the in vitro selection process in order to identify those functional groups most apt for RNA binding.…”
mentioning
confidence: 98%
“…Notably, small molecules have also been proposed to target disease-causing nucleic acid targets and modulate their function 19 . The advantage of this approach is that it would apply the advantages of small molecules to DNA and RNA “receptors”.…”
Section: Targeting Mrna: Principles and Lessons Learnedmentioning
confidence: 99%
“…32-35 Approximating loop stability and probability from sequence is a key to accurate prediction of secondary structure. 6, 36, 37 Moreover, small loops provide benchmarks for testing computational approaches for predicting RNA thermodynamic stability and 3D structure.…”
Section: Introductionmentioning
confidence: 99%